(untitled) (Práxis Educativa, 2009)
Much is said, nowadays, about education on-line, but little is discussed about the presence of the computer and the network at home and its use for educational purposes. The study considered this flaw, based on documents and statistics divulged by foreign and national organisms. The data collected was analyzed from a theoretical perspective based on authors that express a critical view of the use of this technology, such as Dupas (2001), Castells (1999), Lastres (1999), Postman (1994). Among the results of the study, can be distinguished the following: (a) the distribution of domiciles with microcomputer and access to the network is extremely unequal, bounded to the economic level of the region, both in terms of Brazil and the State of Rio de Janeiro, having intimate relation with the bad distribution of telephonic lines; (b) to the bad distribution of telephones and access to the internet another problem is added, that of the presence of providers; what suggests a “domino” effect; (c) 70% of the domiciles of the districts of Botafogo and Humaitá have access to the internet, what place them in a situation similar to Finland, where 73% of the population access the network at home; (d) the educational use of the internet in domiciles of these two districts is significant, while in the Nordic countries is not; (e) there, like in Brazil, the electronic mail is the main use. The use of the network for study/research, made by Botafogo and Humaitá residents, suggests the relevance of educational policies aimed at the development of virtual spaces that favor processes of self-formation. Keywords: Connectivity to the network. Uses of the internet. Place of the educational use.